Contribution to pathophysiological dystrophy treatment - Mongrut Muñoz, Octavio (1950)
One of the most fascinating chapters in the Pediatric Clinic is the study of the physiology and pathology of nutrition, because their influence is reflected markedly in all processes of development and growth of the child, and in maintaining proper immune system against disease.